Pengaruh Kepemimpinan, Motivasi Kerja, dan Disiplin Kerja terhadap Kinerja Guru SDN di Kelurahan Sepanjang Jaya Kota Bekasi - Sevtiani Isty Lazumi; Yayan Hendayana; Sri Wulandari (Indo Publishing, 2026)
This study aims to analyze the influence of leadership, work motivation, and work discipline on the performance of public elementary school teachers in Sepanjang Jaya Village, Bekasi City. This research employed a quantitative method with an associative approach. The sample consisted of 91 teachers selected using a saturated sampling technique. Data were collected through questionnaires and analyzed using IBM SPSS Statistics version 27, including validity, reliability, classical assumption, multiple linear regression, t-test, F-test, and coefficient of determination analyses. The results indicate that leadership, work motivation, and work discipline each have a positive and significant effect on teacher performance. Simultaneously, the three variables also have a positive and significant influence on teacher performance. The coefficient of determination (R²) of 0.415 indicates that 41.5% of the variation in teacher performance is explained by leadership, work motivation, and work discipline, while the remaining 58.5% is influenced by other factors outside the research model.